Transforming traditions into academic resources: Astudy of Chinese scholars in the humanities and social sciences - Yanzhen Zhu (First and Corresponding Author) (Higher Education, 2025)
The asymmetrical global higher education and knowledge systems ordered by Euro–American hegemony have been increasingly interrogated, especially by scholars in the humanities and social sciences (HSS). With gathering awareness, growing HSS scholars from non-Western backgrounds have called for global intellectual pluriversality. Responding to such a trend, this article sheds new light on the status quo of East Asian and other non-Euro–American intellectual traditions by taking Chinese intellectual traditions as a case. Since the nineteenth century, generations of Chinese intellectuals have strived to transform their intellectual traditions into modern resources. This historical mission has been carried on by contemporary scholars and become even more complex in the current global era. By unpacking the real perceptions and recent experiences of Chinese HSS scholars, this study demonstrates that Chinese intellectual traditions deeply influence today’s knowledge production and have been transformed into three kinds of academic resources: approaches, methodologies/paradigms, and theories. However, the transformation process has never been smooth. Domestically, the great endeavours of Chinese HSS scholars are often impeded by the dominant intellectual extraversion and coercive audit culture; internationally, they feel constrained by epistemic injustice. This article proposes an empirical approach to examining and presenting intellectual traditions in the individual experiences of scholars. It reveals the high complexities of navigating through asymmetrical globalisation to achieve intellectual pluriversality.